On Expectations, Realizations and Partial Retirement - Mauro Mastrogiacomo (Tinbergen Institute, 2004)
This study investigates whether many people fear an unexpectedshock in their financial situation around retirement and whether therelated expectations and realizations match each other. We use theDutch Social Economic Panel survey data, where expectations aboutthe next year's financial situation are reported. We show that realizedchanges exceed expectations, and that this finding is more promi-nent around age 65. The descriptive statistics, as well as the non-parametric tests on the conditional distribution of expectations andrealizations, suggest that individuals around retirement are overly pes-simistic and attach more weight to prospective bad events than to goodevents. The model estimates show that their fears are unjustified, inparticular when individuals are highly educated. Further the link he-tween macro shocks, micro-shocks and expectations is investigated.
Keywords: D84; J26; 330; retirement; expectations; non parametric test; Altersgrenze; Erwartungstheorie; Altersvorsorge; Niederlande